1994
DOI: 10.1038/368466a0
|View full text |Cite
|
Sign up to set email alerts
|

An RNA polymerase II holoenzyme responsive to activators

Abstract: RNA polymerase II requires multiple general transcription factors to initiate site-specific transcription. These proteins can assemble in an ordered fashion onto promoter DNA in vitro, and such ordered assembly may occur in vivo (Fig. 1a). Some general transcription factors can interact with RNA polymerase II in the absence of DNA, however, suggesting that RNA polymerase II may also assemble into a multi-component complex containing a subset of initiation factors before binding to promoter DNA (Fig. 1b). Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
487
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(507 citation statements)
references
References 32 publications
18
487
0
2
Order By: Relevance
“…CDK8 (yeast SRB10) and its regulatory partner cyclin C (yeast SRB11) were initially isolated in yeast using a genetic screen for suppressors of truncation mutations in the RNAP II CTD (Koleske et al, 1992;Thompson et al, 1993;Koleske and Young, 1994;Liao et al, 1995). The CDK8-cyclin C complex was subsequently shown to be associated with the RNAP II holoenzyme in yeast (Liao et al, 1995) and in mammalian cells (Ossipow et al, 1995;Maldonado et al, 1996).…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
“…CDK8 (yeast SRB10) and its regulatory partner cyclin C (yeast SRB11) were initially isolated in yeast using a genetic screen for suppressors of truncation mutations in the RNAP II CTD (Koleske et al, 1992;Thompson et al, 1993;Koleske and Young, 1994;Liao et al, 1995). The CDK8-cyclin C complex was subsequently shown to be associated with the RNAP II holoenzyme in yeast (Liao et al, 1995) and in mammalian cells (Ossipow et al, 1995;Maldonado et al, 1996).…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
“…then interacts directly with RNA pol IIa and subsequently recruits TFIIH to the C-terminal domain (CTD) of RNA pol IIa [42]. A large aggregate of proteins known as mediator, consisting of 20 or so proteins, including several suppressors of RNA polymerase B (II) proteins (' SRBs ') [43], then assemble at the CTD of RNA pol IIa [43][44][45].…”
Section: Figure 1 Gtf Assembly At a Typical Eukaryotic Promotermentioning
confidence: 99%
“…More recently a large multisubunit complex known as RNA pol II holoenzyme, containing RNA pol II, TFIIB, TFIIH and mediator [53,54] has been identified that can assemble independently of a promoter [44,45]. The identification of RNA pol II holoenzyme that is capable of responding to enhancers [43] suggests a different model for transcription-apparatus assembly.…”
Section: Figure 1 Gtf Assembly At a Typical Eukaryotic Promotermentioning
confidence: 99%
“…5A). Yeast SUG1 has been shown to be a component of the 1200 kDa yeast RNA polymerase II holoenzyme, which contains TBP and other transcription factors (Thompson et al 1993;Koleske & Young 1994). Since some proteasomal ATPases have the ability to form heterodimers through their leucine zipper-like structures (Ohana et al 1993) various polypeptides are considered to interact with the ATPases.…”
Section: Tbp-atpase-complex With a Molecular Mass Of ϸ800 Kdamentioning
confidence: 99%